2013
DOI: 10.1111/petr.12048
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab induction in pediatric kidney transplantation

Abstract: Recipient parenchymal lymphatic cells are crucial for direct and indirect pathways of allorecognition. We proposed that alemtuzumab, being infused several weeks pretransplant could eradicate peripheral lymphatic cells and promote donor-specific tolerance. We present here a single center, retrospective review of 101 consecutive living-donor kidney transplantations to pediatric patients aged from seven month to 18 yr, performed between September 2006 and April 2010. Immunosupression protocol included two 30 mg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 25 publications
0
25
1
1
Order By: Relevance
“…We have only had one case of CMV viremia and no cases of BK nephropathy despite that our patients continue to be on both calcineurin inhibitor and MMF. Compared to the literature, our infectious complications appear to be lower than reported, but this could be related to our small number of patients . In this study, we show graft survival of 95% and patient survival of 100% at seven yr.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We have only had one case of CMV viremia and no cases of BK nephropathy despite that our patients continue to be on both calcineurin inhibitor and MMF. Compared to the literature, our infectious complications appear to be lower than reported, but this could be related to our small number of patients . In this study, we show graft survival of 95% and patient survival of 100% at seven yr.…”
Section: Discussioncontrasting
confidence: 73%
“…Four-yr follow-up showed promising results in terms of safety, efficacy, and tolerability (13). Kaabak et al (14) modified the Pittsburgh protocol by giving the first dose of alemtuzumab two to three wk prior to living donor kidney transplantation and the second dose on the day of transplantation to achieve maximal lymphocyte depletion. Their results also revealed promising patient and graft survival rates using this strategy.…”
mentioning
confidence: 99%
“…Recent RCT in adults have shown lower frequency of acute rejection in comparison to basiliximab in patients non at high immunological risk [18,19] . In children the first relevant experience was from Kidney Transplantation Center in Moskow, as Kaabak et al [20] reported, in living related pediatric renal transplants. The rationale was to eradicate peripheral lymphomonocytes and induce donor-specific tolerance, by infusing two doses of 30 mg alemtuzumab, one 12-29 d prior to transplantation and the other at surgery.…”
Section: Renal Transplantation In Childrenmentioning
confidence: 99%
“…The specialists are primarily interested in the long-term transplantation results and the factors that affect them. There are only few publications on kidney transplantation in Russia [1][2][3][4]. We would like to bring forward the long-term results of pediatric kidney transplantations not in the traditional form of Kaplan-Meier actuarial survivability estimator, but in the form of the number of people with functioning transplants, who had received their first transplants in childhood.…”
Section: Introductionmentioning
confidence: 99%